ETHNOBOTANICAL STUDY OF THE FALSE BAOBAB (KIGELIA AFRICANA LAM. BENTH) IN THE DISTRICT OF ISSABA (Commune de POBE) - ALI, Rachad Kolawolé Foumilayo Mandus (My University, 2023)
Kigelia africana is one of the poorly understood species. Thus, this study aims to document the different uses of K. africana in the Borough. An ethnobotanical survey was carried out among 71 people in Issaba. The data collected is processed with Excel 2010 and analyzed from ethnobotanical indices. In total 5 categories of uses are recognized for K. africana by local populations among which traditional medicine is the most cited with thirty-one (31) types of uses. The most used organs are the bark (32 %), tpharmaceuticalformsandhe fruit (19 %). Decoction and calcination are the most commonly used are most administered orally and through the skin. In addition, K. africana is abundant in the medium. Despite this abundance, the study also showed that human pressure on the species and its habitat is significant in this locality that it is necessary to define a short-term conservation strategy for the species.
Keywords: Issaba district; Kigelia africana; ethnobotany